2019
DOI: 10.2147/ott.s229514
|View full text |Cite
|
Sign up to set email alerts
|

<p>Emerging Roles Of hsa-circ-0046600 Targeting The miR-640/HIF-1α Signalling Pathway In The Progression Of HCC</p>

Abstract: Purpose: Circular RNAs (circRNAs) play important roles in the development and progression of various human cancers. hsa-circ-0046600 is a circRNA of unknown function. The purpose of this study was to investigate the biological function of hsa-circ-0046600 in hepatocellular carcinoma (HCC) and elucidate the possible molecular mechanisms of this circRNA. Materials and methods: GSE97332, quantitative reverse transcription polymerase chain reaction (qRT-PCR) and fluorescence in situ hybridization (FISH) were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…For example, miR-640 inhibits the formation of capillaries ( 22 ); however, its role in cancer development has not yet been investigated. In their research, Li et al ( 23 ) and Zhai et al ( 24 ) both demonstrated that miR-640 exerts tumor-suppressive effects in ovarian cancer and hepatocellular carcinoma. In another study, miR-640 was reported to enhance the development of prostate cancer ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, miR-640 inhibits the formation of capillaries ( 22 ); however, its role in cancer development has not yet been investigated. In their research, Li et al ( 23 ) and Zhai et al ( 24 ) both demonstrated that miR-640 exerts tumor-suppressive effects in ovarian cancer and hepatocellular carcinoma. In another study, miR-640 was reported to enhance the development of prostate cancer ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by Chi et al suggested that circRNA cir-cPIP5K1A functions as a miR-600 sponge to inhibit miR-600 to disrupt the interaction at the 3'-UTR between HIF-1α and miR-600 to promote HIF-1α posttranscriptional expression, as well as proliferation and metastasis of non-small-cell lung cancer [130]. In addition, in hepatocellular carcinoma, circRNA_0046600 could upregulate HIF-1α by sponging miR-640 to promote cancer progression [131]. CircRNAs are a novel research focus,, so no additional studies on the regulatory roles of circRNAs in HIF-1α expression are currently available.…”
Section: Posttranscriptional Regulation Of Hif-1α Expression By Ncrnasmentioning
confidence: 99%
“…gallbladder cancer promotes migration, invasion and EMT post-transcriptional regulation [122] lncRNA PVT1 lung cancer promotes viability and proliferation post-transcriptional regulation [123] lncRNA HOTAIR renal cancer promotes proliferation, migration and EMT, inhibits apoptosis post-transcriptional regulation [124] lncRNA ROR hepatocellular cancer promotes viability post-transcriptional regulation [125] lncRNA NEAT1 osteosarcoma promotes proliferation and invasion post-transcriptional regulation [126] lncRNA UCA1 acute myelocytic leukemia promotes glycolysis and chemoresistance post-transcriptional regulation [127] lncRNA PVT1 gastric cancer promotes proliferation and invasion post-transcriptional regulation [128] lncRNA DANCR nasopharyngeal carcinoma promotes invasion and metastasis post-transcriptional activation via ILF3/ ILF2 [129] circPIP5K1A lung cancer promotes proliferation and metastasis post-transcriptional regulation [130] circRNA_0046600 hepatocellular carcinoma promotes migration post-transcriptional regulation [131] miR-214 lung cancer promotes invasion, proliferation and migration transcriptional activation via ING4 [132] miR-206 lung cancer inhibits proliferation and angiogenesis, promotes apoptosis transcriptional inhibition via 14-3-3ζ/STAT3 axis [133] miR-675-5p glioma promotes angiogenesis stabilize the mRNA via HuR [134] lncRNA CPS1-IT1 hepatocellular cancer inhibits EMT, proliferation, migration and invasion transcriptional inhibition via Hsp90 [135] lncRNA PVT1 gastric cancer promotes survival, inhibits apoptosis transcriptional activation via mTOR [136] has no effect on HIF-1α degeneration but acts as an adapter protein to recruit transcriptional repressors to regulate HIF activity [157]. MiR-206 can attenuate the growth and angiogenesis of non-small-cell lung cancer cells through the 14-3-3z/STAT3/HIF-1α/VEGF pathway.…”
Section: Transcriptional Regulation Of Hif-1α Expression By Ncrnasmentioning
confidence: 99%
“…Last but not least, circRNAs and HIF‐1α also closely interact. In hepatocellular carcinoma, has‐circ‐0046600 enhanced the expression of HIF‐1α through competitive binding with miR‐640 15 . In addition, knockdown of circ_PIP5K1A suppressed HIF‐1α by promoting the sponging of miR‐600 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In hepatocellular carcinoma, has-circ-0046600 enhanced the expression of HIF-1α through competitive binding with miR-640. 15 In addition, knockdown of circ_PIP5K1A suppressed HIF-1α by promoting the sponging of miR-600. 16 In summary, cir-cRNAs exerted dramatic effects on hypoxia and atherosclerosis; however, the role of circRNAs/HIF-1α in atherosclerosis needs to be further explored.…”
mentioning
confidence: 99%